2005
DOI: 10.1124/jpet.104.076133
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Dosing with Anti-Interleukin-13 Monoclonal Antibody Inhibits Asthma Progression in Mice

Abstract: In vivo models have demonstrated that interleukin-13 (IL-13) plays an important role in asthma; however, few studies have evaluated the effect of inhibition of IL-13 on established and persistent disease. In the present study, we have investigated the effect of a therapeutic dosing regimen with an anti-IL-13 monoclonal antibody (mAb) in a chronic mouse model of persistent asthma. BALB/c mice were sensitized to allergen [ovalbumin (OVA); on days 1 and 8] and challenged with OVA weekly from day 22. Anti-IL-13 mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 41 publications
(61 reference statements)
3
49
1
2
Order By: Relevance
“…IL-13 is a pleiotropic cytokine produced mainly by T cells and is critical for the development of airway hyperresponsiveness (AHR) associated with allergen exposure [18]. It has indeed been reported that treatment of mice with anti-IL-13 mAb inhibited AHR [19,20] and that Il-13-induced airway inflammation might involve a direct effect on airway smooth muscles [21]. Our results strongly suggest that IL-13 production is intrinsically different in the two mouse strains and accounts for the increased bronchial hyperresponsiveness in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 is a pleiotropic cytokine produced mainly by T cells and is critical for the development of airway hyperresponsiveness (AHR) associated with allergen exposure [18]. It has indeed been reported that treatment of mice with anti-IL-13 mAb inhibited AHR [19,20] and that Il-13-induced airway inflammation might involve a direct effect on airway smooth muscles [21]. Our results strongly suggest that IL-13 production is intrinsically different in the two mouse strains and accounts for the increased bronchial hyperresponsiveness in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse asthma model, treatment with an anti-IL-13 mAb prevented progression of inflammation by inhibiting the expression of cytokines and chemokines, such as TNF-␣ and MIP-1␣ (34,35). In addition, in endothelial cells, IL-13 induced NADPH oxidase activation and consequent production of ROS (36), possibly leading to oxidative damage and eventual cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas several studies have reported beneficial effects of IL-13, such as increased survival of mice in an experimental model of sepsis (33), harmful effects of IL-13 are also documented. For instance, in a mouse asthma model, allergic airway inflammation is inhibited by treatment with an anti-IL-13 mAb (34,35). Additionally, in endothelial cells, IL-13 induces ROS production via activation of NADPH oxidase (36).…”
mentioning
confidence: 99%
“…In contrast, inhibition of IL-13, another Th 2 cytokine whose signal transduction pathway overlaps with that of IL-4, completely blocks airway hyperreactivity, subepithelial fibrosis and progression of inflammation in mouse asthma models. These effects were associated with an inhibition of MMP-9, neutralisation of IL-13 resulting in a reduction in total proteins MMP-9 levels in the lung tissue of mice (Yang et al, 2005).…”
Section: Interactions Between Mmps and Cytokines -Growth Factors In Amentioning
confidence: 95%
“…In contrast, inhibition of IL-13, another Th 2 cytokine whose signal transduction pathway overlaps with that of IL-4, completely blocks airway hyperreactivity, subepithelial fibrosis and progression of inflammation in mouse asthma models. These effects were associated with an inhibition of MMP-9, neutralisation of IL-13 resulting in a reduction in total proteins MMP-9 levels in the lung tissue of mice (Yang et al, 2005).Some Th 2 cytokines contribute in a significant manner to pathology of asthma and other lung inflammatory diseases by interacting directly with MMPs or TIMPs resulting in an increase or decrease of their expression and activity. IL-4 decreased MMP-2 protein and mRNA levels in human bronchial fibroblasts in culture but did not alter TIMP-2 production leading to an increased TIMP-2/MMP-2 ratio.…”
mentioning
confidence: 99%